Argumentative uses of “pero” in spanish digital media - Pedro, Carolina da Costa [UNESP]; Garcia, Talita Storti [UNESP] (Faculdade de Letras da UFMG, 2021)
This paper intends to present an analysis of two uses of adversative conjunction pero found in a Spanish written corpus in digital media. The theoretical-methodological apparatus used is the Functional Discourse Grammar – FDG (HENGEVELD; MACKENZIE, 2008). According to RAE (2009), pero is coordinative conjunction in which presents two opposing clauses. From the point of view of FDG, however, these two units configure Discourse Acts in an unequal relationship, which engender Concession rhetorical function. The speaker presents an Act to grant information in order to then present another Act that he considers arguably more relevant. Some of the uses found in this study are beyond that interpretation. The research universe consists of data collected from blogs and extracted from CORPES (Corpus del Español del Siglo XXI), from the Real Academia Española. It was verified that, besides being used between two Discourse Acts, it can also introduce Moves and also emphasize a Subact previously presented, being a valuable element for the speaker’s argument.
Usos argumentativos de “pero” em meios digitais espanhóis
Keywords: Argumentation; Pero; Rhetoric; Spanish